Intra‐industry bankruptcy contagion: Evidence from the pricing of industry recovery rates. (3rd June 2019) - Chang, Yuanchen; Hsieh, Yi‐Ting; Liu, Wenchien; Miu, Peter
Abstract: How does bankruptcy contagion propagate among industry peers? We study the debt recovery channel of industry contagion by examining whether the cost of a company's debt is affected by the observed recovery rates of its bankrupt industry peers. Our results show that lower industry recovery rates are associated with higher loan spreads, but only when the contracts were originated during industry bankruptcy waves. Consistent with the debt recovery channel of industry contagion, we find that the negative effects of industry recovery rates are significantly stronger under situations where the effect is expected to be more salient.